Pengaruh Relationship Marketing Dan Kualitas Produk Terhadap Loyalitas Pelanggan Dengan Kepuasan Konsumen Sebagai Variabel Intervening : Studi Kasus Pada Katering Zahdan Kamal Sentosa - Ainul Musyafiah; Roby Setiadi; Syariefful Ikhwan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The research aims to find out how relationship marketing and product quality influence customer loyalty through customer satisfaction at Zahdan Kamal Sentosa catering. This research a quantitative descriptive research type using AMOS 22 Structural Equating Modelling (SEM) analysis. The population used in this research is catering customer in 2022 with a total of 143 respondents. The results showed that relationship marketing had a positive effect on cunsomer satisfaction and customer loyalty with a CR value of 2.279 and 2.958 (CR ≥ 1.96) respectively and a probability value of 0.003 and 0.023 (P ≤ 0.05). Product quality variable has a positive effect on customer satisfaction with a CR value 2.867 (CR ≥ 1.96) and the probability value is 0.004 (p ≤ 0.05). The product quality variable does not have a positive effect on customer loyalty because the CR value is 1.239 (CR ≤ 1.96) and the probability is 0.215 (p ≥ 0.05). the consumer satisfaction variable has a positive effect on loyalty customer with a CR value of 2.294 (CR ≥ 1.96) and a probability value of 0.022 (p ≤ 0.05).